2006
DOI: 10.1111/j.1468-1331.2006.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurocutaneous syndrome with mental delay, autism, blockage in intracellular vescicular trafficking and melanosome defects

Abstract: We evaluated a 11-year-old male patient with mental delay, autism and brownish and whitish skin spots. The former resembled those of neurofibromatosis, the latter those of tuberous sclerosis. The patient received a complete clinical work-up to exclude neurofibromatosis, tuberous sclerosis, or any other known neurocutaneous disease, with biochemistry, chromosome analysis and analysis of skin specimens. Being all the other tests not significant, two main ultrastructural defects were observed. The first was a blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Nevertheless, no relevant studies or case reports were identified during the last decade, probably diminishing the possibility of this association), Jacobsen syndrome [Fisch et al, 2010], Joubert syndrome (Although there are a few case reports of Joubert patients with ASD [Holroyd et al, 1991; Ozonoff et al, 1999; Kumandas et al, 2004], there is more recent opposite evidence, supporting that the two disorders are distinct [Braddock et al, 2006] and their clinical similarities may be due to cerebellar abnormalities present in both conditions. Nevertheless, common variation in AHI1 , which causes Joubert syndrome type 3, was reported to contribute to ASD risk [Alvarez Retuerto et al, 2008]), Juvenile dentatorubral‐pallidoluysian atrophy [Licht and Lynch, 2002], Kabuki syndrome or Niikawa–Kuroki syndrome [Ho and Eaves, 1997; Akin Sari et al, 2008], KBG syndrome [Hah et al, 2009], Kleefstra Syndrome (http://www.ncbi.nlm.nih.gov/pubmed?term=kleefstra%20pagon), Kleine Levin syndrome [Berthier et al, 1992; Mukaddes et al, 2009], Leber's congenital amaurosis (The initial association with ASD [Rogers and Newhart‐Larson, 1989] has been diminished by recent studies reporting mild only autistic traits in a small minority of children with Leber's [Fazzi et al, 2007; den Hollander et al, 2008]), Leopard syndrome [Watanabe et al, 2010], Leukocyte adhesion deficiency type II [Gazit et al, 2010], Marineso Sjogren syndrome [Sponheim and Skjeldal, 1998], Miller–Dieker syndrome (two personal cases), MOMO syndrome [Giunco et al, 2008], Myhre syndrome [Titomanlio et al, 2001], Neuroaxonal dystrophy [Weidenheim et al, 2001], New neurocutaneous syndrome [Buoni et al, 2006; Zannolli et al, 2008], Nicolaides–Baraitser syndrome [Gana et al, 2011], Noonan syndrome [Ghazziudin et al, 1994], Ocolocutaneous albinism [Delong, 2007; Bakare and Ikegwuonu, 2008], Orstavik syndrome [Orstavik et al, 1997], PARK2 microdeletion/microduplication syndrome [Scheuerle and Wilson, 2011], Potocki–Shaffer syndrome [Swarr et al, 2010]. Rett syndrome variants (e.g., FOXG1 syndrome or Zapella variant) [Renieri et al, 2009; Kortüm et al, 2011], Rubinstein taybi syndrome [Levitas and Reid, 1998; Hellings et al, 2002; Schorry et al, 2008; Galéra et al, 2009], Septo optic dysplasia [Polizzi et al, 2006; Parr et al, 2010], Sturge–Weber syndrome (three personal cases) Trichothiodystrophy syndrome [Schepis et al, 1997], Unilateral cerebellar hypoplasia [Ramaekers et al, 1997], Unilateral ...…”
Section: Other Syndromesmentioning
confidence: 99%
“…Nevertheless, no relevant studies or case reports were identified during the last decade, probably diminishing the possibility of this association), Jacobsen syndrome [Fisch et al, 2010], Joubert syndrome (Although there are a few case reports of Joubert patients with ASD [Holroyd et al, 1991; Ozonoff et al, 1999; Kumandas et al, 2004], there is more recent opposite evidence, supporting that the two disorders are distinct [Braddock et al, 2006] and their clinical similarities may be due to cerebellar abnormalities present in both conditions. Nevertheless, common variation in AHI1 , which causes Joubert syndrome type 3, was reported to contribute to ASD risk [Alvarez Retuerto et al, 2008]), Juvenile dentatorubral‐pallidoluysian atrophy [Licht and Lynch, 2002], Kabuki syndrome or Niikawa–Kuroki syndrome [Ho and Eaves, 1997; Akin Sari et al, 2008], KBG syndrome [Hah et al, 2009], Kleefstra Syndrome (http://www.ncbi.nlm.nih.gov/pubmed?term=kleefstra%20pagon), Kleine Levin syndrome [Berthier et al, 1992; Mukaddes et al, 2009], Leber's congenital amaurosis (The initial association with ASD [Rogers and Newhart‐Larson, 1989] has been diminished by recent studies reporting mild only autistic traits in a small minority of children with Leber's [Fazzi et al, 2007; den Hollander et al, 2008]), Leopard syndrome [Watanabe et al, 2010], Leukocyte adhesion deficiency type II [Gazit et al, 2010], Marineso Sjogren syndrome [Sponheim and Skjeldal, 1998], Miller–Dieker syndrome (two personal cases), MOMO syndrome [Giunco et al, 2008], Myhre syndrome [Titomanlio et al, 2001], Neuroaxonal dystrophy [Weidenheim et al, 2001], New neurocutaneous syndrome [Buoni et al, 2006; Zannolli et al, 2008], Nicolaides–Baraitser syndrome [Gana et al, 2011], Noonan syndrome [Ghazziudin et al, 1994], Ocolocutaneous albinism [Delong, 2007; Bakare and Ikegwuonu, 2008], Orstavik syndrome [Orstavik et al, 1997], PARK2 microdeletion/microduplication syndrome [Scheuerle and Wilson, 2011], Potocki–Shaffer syndrome [Swarr et al, 2010]. Rett syndrome variants (e.g., FOXG1 syndrome or Zapella variant) [Renieri et al, 2009; Kortüm et al, 2011], Rubinstein taybi syndrome [Levitas and Reid, 1998; Hellings et al, 2002; Schorry et al, 2008; Galéra et al, 2009], Septo optic dysplasia [Polizzi et al, 2006; Parr et al, 2010], Sturge–Weber syndrome (three personal cases) Trichothiodystrophy syndrome [Schepis et al, 1997], Unilateral cerebellar hypoplasia [Ramaekers et al, 1997], Unilateral ...…”
Section: Other Syndromesmentioning
confidence: 99%
“…6 Light microscopy of the biopsy obtained from the hyperpigmented skin revealed high degree of pigmentation up to the upper epidermal layers, while the electron microscopy showed several melanosome abnormalities such as increased number and abnormal maturation. 7,8 Chromosome studies from fibroblast cultures usually show normal karyotypes. 2,3,7,9 However, chromosomal mosaicism in fibroblast cultures is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Chromosome studies from fibroblast cultures usually show normal karyotypes. 2,3,7,9 However, chromosomal mosaicism in fibroblast cultures is also possible. 2,10,11 Cutis tricolor is associated with multisystem birth defects such as craniofacial anomalies including hypertelorism, epicantal folds, wide philtrum, backward rotated ears, brushy eyebrows, deep nasal bridge with broad nostrils, mental and motor retardation, epileptic seizures, a behavioural phenotype, severe kyphoscoliosis and non-specific brain abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A common polymorphism in the HOXA1 gene is associated with a susceptibility to autism spectrum disorder (Ingram et al., 2000). Interestingly, some neurocutaneous syndromes present autism and melanosome defects (Buoni et al., 2006). Altogether, one may wonder if there is a connection between HOXA1, melanomagenesis and autism.…”
mentioning
confidence: 99%